2019
DOI: 10.1093/biolinnean/blz151
|View full text |Cite
|
Sign up to set email alerts
|

Genital coupling, morphology and evolution of male holding structures in Cicadinae (Hemiptera: Cicadidae)

Abstract: Male and female genitalia include some of the most complex and morphologically diverse structures in Metazoa. Ornamentations in genitalia have been studied in several groups, and a variety of functional roles have been proposed. Although complex features of the genitalia have been observed in internal genitalia in cicadas, their functions have not yet been elucidated. These ornamentations, together with precopulatory sexual selection, make cicadas good models for evolutionary studies on genital coupling. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Measurements of the new species were made with Vernier calipers. The terminology used in descriptions generally follows Moulds (2005Moulds ( , 2012, except for de-tails of genital morphology (Marshall et al, 2018;Ruschel et al, 2019). Photographs were taken using a Nikon AZ100M stereomicroscope and NIS-Elements Advanced Research software available at the Departamento de Zoologia, Universidade Federal do Rio Grande do Sul (UFRGS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of the new species were made with Vernier calipers. The terminology used in descriptions generally follows Moulds (2005Moulds ( , 2012, except for de-tails of genital morphology (Marshall et al, 2018;Ruschel et al, 2019). Photographs were taken using a Nikon AZ100M stereomicroscope and NIS-Elements Advanced Research software available at the Departamento de Zoologia, Universidade Federal do Rio Grande do Sul (UFRGS).…”
Section: Methodsmentioning
confidence: 99%
“…The exceedingly long and undivided male uncus may be correlated to the shape of the female sternite VII. During copula, the male places the uncus into the groove of female sternite VII (Ruschel et al, 2019), and the variation in the width of the groove width seems to be associated to the width of uncus. Selymbria chevauxensis and S. stigmatica males have a flat uncus (fig.…”
Section: Morphologymentioning
confidence: 99%
“…We used the maximum width of the external male genitalia as a proxy for genital size and the maximum abdominal width as a proxy for body size. Genital width was chosen due to its documented role in genital coupling with females ( Singh-Pruthi 1925 ; Moreno-García and Cordero 2008 ; Wang et al 2009 ; Genevcius and Schwertner 2017 ; Ruschel et al 2019 ; and see introduction). The majority of measures were collected directly from scaled images published in the literature or online databases, but a few species were measured from personal figures ( supplementary data S2, Supplementary Material online).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to study genital size, more specifically width, due to its demonstrated role in mating for the Hemiptera. Studies with different families have documented a correspondence between the width of the external genitalia in males and females ( Moreno-García and Cordero 2008 ; Wang et al 2009 ; Genevcius et al 2017 ; Ruschel et al 2019 ). The male capsule attaches horizontally to the female plates providing the mechanical stability in copula ( Genevcius and Schwertner 2017 ).…”
Section: Introductionmentioning
confidence: 99%